The Contextuality of Asbāb al-Nuzūl in Interpreting QS. al-Ahzāb [33]:4 and QS. al-Taḥrĭm [66]:1 - Mufassirotul Bayaqi; Abdullah Faqih Hikami; Muhammad Abbel Saktya Nugraha (Jurnal test, 2026)
QS. al-Ahzāb: 4 and QS. al-Taḥrīm: 1 with an emphasis on the relationship between the text of revelation and socio-historical reality. QS. al-Ahzāb: 4 is studied in the context of the practices of zhihār and tabannī that were developing in pre-Islamic society, which often gave rise to unclear lineage and injustice in the family structure. This verse emphasizes the Qur’anic correction of these practices by placing lineage and injustice within the family structure. QS. al-Taḥrīm verse 1 is analyzed through the dynamics of the Prophet’s household, particularly regarding his oath prohibiting something halal (permissible) in order to calm the jealousy of his wives. Allah’s rebuke in this verse emphasizes the boundaries of morality and the domestic sphere while also strengthening the principle that the determination of halal and haram cannot be determined by emotional considerations alone. This study aims to reveal how these two verses reflect the process of social, legal, and moral reform brought by the Qur’an. This research uses a historical-descriptive method, namely, uncovering the history of the two verses to reveal their contextual meaning. The analysis used in this study is contextual analysis, linking the interpretation results to the reasons for their revelation. These two verses demonstrate the Qur’an’s active response to social situations and emphasize the goal of fostering law and ethics that align with justice and the common good. This research emphasizes the importance of contextualization in understanding the normative role of the Qur’an.